Paediatric ophthalmology at primary healthcare level - Mpopi Lenake; Nagib du Toit (South African Family Practice)
Paediatric patients make up a significant portion of the patient load at primary care level. Children can present at the primary care physician with a wide range of eye problems, some of which are serious enough to impair the quality of the child’s life. The aim of this review article was to highlight serious paediatric visual disorders of which the primary care practitioner should be aware. The article includes a brief discussion of the features of amblyopia, strabismus, retinopathy of prematurity, allergic conjunctivitis, ophthalmia neonatorum and retinoblastoma. Causes of sight-threatening conditions are highlighted, and methods to detect them at primary care level described. Paediatric eye disorders are relatively common and need to be identified and managed as early as possible in order to prevent a potential lifetime of visual morbidity, blindness or worse.